A calcium-based adsorbent and its preparation method and application
By adding bioglue and using calcium-containing solid waste in the preparation process of calcium-based adsorbent, the problem of calcium-based adsorbents being easily sintered and agglomerated at high temperatures is solved, its adsorption performance and stability are improved, and production costs are reduced.
Patent Information
- Application Number
- CN202411872678.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-01
AI Technical Summary
Existing calcium-based adsorbents are prone to sintering, agglomeration and structural collapse when used at high temperatures, resulting in a decrease in adsorption performance and stability.
Calcium-based adsorbent with stable pore structure and high Taman temperature are prepared by adding bioglue as pore-forming agent in the preparation process of calcium-based adsorbent, and using calcium-containing solid waste as calcium source, cement as a binder, and calcining and extrusion.
It improves the anti-sintering performance and cycle stability of calcium-based adsorbents, maintains long-term stability and high adsorption capacity, and reduces production costs and resource consumption.
Smart Images

Figure CN119733480A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon dioxide capture, and in particular relates to a calcium-based adsorbent and a preparation method and application thereof. Background Art
[0002] As global warming and climate change issues intensify, effectively controlling carbon dioxide (CO2) emissions has become a global focus. Although traditional carbon dioxide capture technology has achieved certain results in industrial applications, it still faces problems such as high cost, high energy consumption, and poor selectivity. Therefore, the development of efficient and low-cost CO2 capture materials has become one of the current research hotspots.
[0003] Calcium-based adsorbents have attracted extensive attention due to their excellent chemical stability, high adsorption capacity and suitable reaction rate. Calcium-based materials can be modified in a targeted manner through different synthesis methods (such as sol-gel method, hydrothermal synthesis method, etc.) to enhance their adsorption performance. However, traditional preparation methods often require the use of expensive raw materials and generate a large amount of production waste, which is not conducive to the sustainable use of resources. In addition, the mechanism of carbon dioxide capture using calcium-based adsorbents is that CaO reacts with CO2 at high temperature to generate CaCO3. The reaction temperature is usually 600-750℃, while the Tammann temperature of calcium carbonate is about 530℃, which is much lower than the reaction temperature. Therefore, during the high-temperature adsorption process, calcium carbonate is prone to sintering and conversion to liquid or decomposition into other compounds. This makes traditional calcium-based adsorbents prone to sintering, agglomeration and structural collapse after multiple cycles of high-temperature adsorption and desorption, resulting in a decrease in the adsorption performance and stability of calcium-based adsorbents for carbon dioxide. Therefore, there is an urgent need to develop a calcium-based adsorbent with good adsorption performance and high stability. Summary of the invention
[0004] In view of the above-mentioned deficiencies, the object of the present invention is to provide a calcium-based adsorbent and a preparation method and application thereof, so as to solve the technical problems of poor adsorption and stability of existing calcium-based adsorbents.
[0005] To achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a method for preparing a calcium-based adsorbent, comprising the following steps: preparing a pore-forming agent solution; wherein the pore-forming agent in the pore-forming agent solution is biological glue; Mixing the calcium source, the binder and the pore-forming agent solution uniformly to obtain a mixed solution; removing the solvent from the mixed solution to obtain a mixed material; The mixed material is calcined until the pore former in the mixed material is decomposed to obtain a calcium-based adsorbent.
[0006] Preferably, the biological glue is one or more of gelatin, bone glue, pectin and hide glue.
[0007] Preferably, the calcium source is calcium-containing solid waste; and the binder is cement.
[0008] Preferably, in the mixed solution, the mass ratio of the pore former, the binder and the calcium source is (2.5-25):5:(20-42.5).
[0009] Preferably, the calcination temperature is 600-800° C. and the calcination time is 1-2 h.
[0010] Preferably, the preparation method further comprises the following steps: extruding, grinding and screening the material obtained after calcination to obtain a calcium-based adsorbent.
[0011] Preferably, the extrusion pressure is 1-20 kN.
[0012] In a second aspect, the present invention provides a calcium-based adsorbent, which is prepared by the preparation method described in the first aspect.
[0013] Preferably, the particle size of the calcium-based adsorbent is 0.25-0.38 mm.
[0014] In a third aspect, the present invention provides a use of the calcium-based adsorbent as described in the second aspect in the cyclic adsorption of carbon dioxide.
[0015] The beneficial effects of the present invention are: 1. The present invention adds bio-gum as a pore-forming agent during the preparation of the calcium-based adsorbent. Since the bio-gum contains macromolecular polysaccharides and proteins, it will decompose during the calcination process, so that a stable pore structure can be formed inside the calcium-based adsorbent, and carbonized products with high nitrogen and sulfur content can be formed, thereby improving the anti-sintering performance of the calcium-based adsorbent and improving the cyclic stability of the calcium-based adsorbent.
[0016] 2. The present invention uses calcium-containing solid waste as a calcium source, which not only reduces resource consumption and pollution, but also the metal oxides contained in the calcium-containing solid waste can react with calcium oxide to generate an inert skeleton, which can increase the Tamman temperature of the calcium-based adsorbent, thereby maintaining the long-term stability and high adsorption capacity of the calcium-based adsorbent.
[0017] 3. The present invention extrude the material obtained after calcination to obtain a calcium-based adsorbent with a denser structure. It not only has uniform particle size and is easy to fluidize and circulate in the calcium circulation system, but also has good reactivity with CO2 and anti-wear ability.
[0018] 4. The present invention does not require the use of harsh conditions such as acid, alkali or sealing, the preparation method is simple, the production process does not generate toxic waste, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.
[0020] Figure 1 is the initial adsorption capacity of CO2 by the calcium-based adsorbents prepared in Examples 1 to 6 and Comparative Examples 1 to 2; Figure 2 is the adsorption capacity of CO2 in the second cycle of the calcium-based adsorbents prepared in Examples 1 to 6 and Comparative Examples 1 to 2; Figure 3 is the total adsorption of CO2 by the calcium-based adsorbents prepared in Examples 1 to 6 and Comparative Examples 1 to 2 after two cycles; Figure 4 These are the mechanical strength test results of the calcium-based adsorbents prepared in Example 1 and Example 7. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The mechanism of capturing carbon dioxide using calcium-based adsorbents is as follows: CaO + CO2 ⇌ CaCO3. The forward reaction is the adsorption of carbon dioxide, and the reaction temperature is usually 600-750°C, and the reverse reaction is the desorption of carbon dioxide, and the reaction temperature is usually 800-950°C. However, the current calcium-based adsorbents are prone to sintering, agglomeration, and structural collapse during use, which seriously affects their adsorption performance and stability. In view of this, an embodiment of the present invention provides a method for preparing a calcium-based adsorbent, comprising the following steps: (1) Adding biological glue into a solvent to obtain a pore-forming agent solution; wherein the biological glue is one or more of gelatin, bone glue, pectin, and hide glue.
[0023] (2) Adding a calcium source and a binder to a pore-forming agent solution and mixing them evenly to obtain a mixed solution; the calcium source is calcium-containing solid waste, including but not limited to one or more of carbide slag, steel slag, and white mud; and the binder is cement. In the mixed solution, the mass ratio of the pore-forming agent, the binder, and the calcium source is (2.5-25):5:(20-42.5).
[0024] (3) Removing the solvent from the mixed solution to obtain a mixed material.
[0025] (4) Calcine the mixture at 600-800°C for 1-2 h to obtain a calcined material.
[0026] (5) The calcined material is extruded at 1-20 kN, and after grinding and screening, a calcium-based adsorbent is obtained.
[0027] The calcium-based adsorbent prepared by the preparation method of the present invention not only has high CO2 adsorption activity, but also has high-temperature stability. It still has high CO2 adsorption activity after multiple carbonation-calcination cycles, and can meet the requirements of the circulating fluidized bed process in terms of strength, wear resistance and particle morphology.
[0028] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be described in further detail below.
[0029] Example 1 (1) Add 2.5 g of gelatin to 100 mL of deionized water and heat in a 60°C water bath until the gelatin is dissolved to obtain a gelatin solution.
[0030] (2) Weigh 5 g of cement and 42.5 g of carbide slag, mix them evenly, add them to the gelatin solution, and treat them by ultrasonic treatment at 60°C for 1 h to obtain a mixed solution.
[0031] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0032] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0033] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0034] Example 2 (1) Add 2.5 g of pectin to 100 mL of deionized water and heat in a 60°C water bath until the pectin is dissolved to obtain a pectin solution.
[0035] (2) Weigh 5 g of cement and 42.5 g of carbide slag, mix them evenly, add them to the pectin solution, and treat them by ultrasonic treatment at 60 °C for 1 h to obtain a mixed solution.
[0036] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0037] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0038] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0039] Example 3 (1) Add 2.5 g of bone gelatin into 100 mL of deionized water and heat in a 60°C water bath until the bone gelatin is dissolved to obtain a bone gelatin solution.
[0040] (2) Weigh 5 g of cement and 42.5 g of carbide slag, mix well, add to the gelatin solution, and treat with ultrasound at 60°C for 1 h to obtain a mixed solution.
[0041] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0042] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0043] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0044] Example 4 (1) Add 2.5 g of hide glue into 100 mL of deionized water and heat in a 60°C water bath until the hide glue is dissolved to obtain a hide glue solution.
[0045] (2) Weigh 5 g of cement and 42.5 g of carbide slag, mix them evenly, add them to the hide glue solution, and treat them by ultrasonic treatment at 60 °C for 1 h to obtain a mixed solution.
[0046] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0047] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0048] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0049] Example 5 (1) Add 5 g of pectin to 100 mL of deionized water and heat in a 60°C water bath until the pectin is dissolved to obtain a pectin solution.
[0050] (2) Weigh 5 g of cement and 40 g of carbide slag, mix them evenly, add them to the pectin solution, and treat them by ultrasonic treatment at 60°C for 1 h to obtain a mixed solution.
[0051] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0052] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0053] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0054] Example 6 (1) Add 25 g of pectin to 100 mL of deionized water and heat in a 60°C water bath until the pectin is dissolved to obtain a pectin solution.
[0055] (2) Weigh 5 g of cement and 20 g of carbide slag, mix them evenly, add them to the pectin solution, and treat them by ultrasonic treatment at 60°C for 1 h to obtain a mixed solution.
[0056] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0057] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0058] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0059] Example 7 (1) Add 2.5 g of gelatin to 100 mL of deionized water and heat in a 60°C water bath until the gelatin is dissolved to obtain a gelatin solution.
[0060] (2) Weigh 5 g of cement and 42.5 g of carbide slag, mix them evenly, add them to the gelatin solution, and treat them by ultrasonic treatment at 60°C for 1 h to obtain a mixed solution.
[0061] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0062] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0063] (5) Grind the calcined material to less than 40 mesh and sieve it through a standard sieve to obtain nearly spherical particles with a particle size of 0.25~0.38 mm, which is the calcium-based adsorbent.
[0064] Comparative Example 1 (1) Take 100 mL of deionized water and place it in a 60℃ water bath and heat it to 60℃.
[0065] (2) Weigh 5 g of cement and 42.5 g of carbide slag, mix them evenly, add them into deionized water, and treat them by ultrasonic treatment at 60°C for 1 h to obtain a mixed solution.
[0066] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0067] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0068] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0069] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that conventional carbon-based materials are used as pore-forming agents. The specific preparation method is as follows: (1) Add 2.5 g of cellulose to 100 mL of deionized water and heat in a 60°C water bath to obtain a cellulose dispersion.
[0070] (2) Weigh 5 g of cement and 42.5 g of carbide slag, mix them evenly, add them to the cellulose dispersion, and treat them by ultrasonic treatment at 60 °C for 1 h to obtain a mixed solution.
[0071] (3) The mixed solution was placed in an oven at 80°C for 24 h to remove the moisture contained therein and obtain a dried mixed material.
[0072] (4) The dried mixed material is ground to a size below 100 mesh, placed in a muffle furnace, and calcined at 700°C for 1 h to obtain a calcined material.
[0073] (5) The calcined material is extruded through an extrusion die of a tablet press to obtain a short cylindrical material with a diameter of 1.5 cm, wherein the extrusion pressure is 5 KN. Subsequently, the extruded material is ground to less than 40 mesh and sieved through a standard sieve to obtain nearly spherical particles with a particle size of 0.25-0.38 mm, which is the calcium-based adsorbent.
[0074] Performance Testing (1) Carbon dioxide adsorption effect and stability of recycling The calcium-based adsorbents of Examples 1 to 6 and Comparative Examples 1 to 2 were tested for adsorption / desorption performance on a thermogravimetric analyzer. Carbon dioxide adsorption / desorption conditions: adsorption temperature 650°C, insulation time 30 min, atmosphere is a mixed gas of 15 vol.% CO2 and 85 vol.% N2; desorption temperature 850°C, insulation time 10 min, atmosphere is 100 vol.% N2. The adsorption capacity of the adsorbent, that is, the mass of CO2 adsorbed per unit mass of the adsorbent, was obtained by recording the mass change of the adsorbent by the thermogravimetric analyzer. The results are shown in FIG. Figures 1 to 3 shown.
[0075] from Figures 1 to 3 It can be seen that the adsorbent prepared by the present invention has good carbon dioxide adsorption / desorption performance. Compared with the adsorbent without biogel pore-forming agent, the first cycle adsorption performance is improved by 15% to 40%, the second cycle adsorption performance is improved by 30% to 47%, and the cumulative performance of the two cycles is improved by 22% to 44%. Compared with the adsorbent with cellulose as a pore-forming agent, the second cycle adsorption amount and the total adsorption amount of the two cycles of the adsorbent of the present invention are higher than those of comparative example 2. Figure 3As shown, the total adsorption amount of two cycles in Example 1 is 17% higher than that of two cycles in Comparative Example 2. The above results show that the calcium-based adsorbent prepared by using bio-gum as a pore-forming agent in the present invention has good CO2 adsorption capacity and cycle stability. This is because the bio-gum contains macromolecular polysaccharides and proteins, which will decompose during the calcination process, so that a stable pore structure is formed inside the calcium-based adsorbent, and after decomposition, carbonization products containing nitrogen, sulfur, etc. are produced, thereby improving the anti-sintering performance of the calcium-based adsorbent; while pure carbon-based materials such as cellulose are decomposed to obtain materials such as carbon black, which show poor cycle stability during high-temperature adsorption / desorption.
[0076] (2) Mechanical properties test The mechanical properties of the calcium-based adsorbents of Example 1 and Example 7 were tested on the wear tester. Mechanical properties test conditions: Weigh 1g of adsorbent particles, place them on the particle wear tester, set the parameters, and rotate them for 1000 revolutions. After the wear test, the particles with a particle size range of 0.25-0.38mm were sieved through a standard sieve and weighed. The results are shown in Figure 2. Figure 4 shown.
[0077] from Figure 4 It can be seen that the adsorbent particles prepared in Example 1, after the loss test of 5000 revolutions, have a proportion of 82.6% of the adsorbent particles with fluidization characteristics, which can meet the requirements of the circulating fluidized bed process and can be used in a fluidized bed reactor. In contrast, after the same 5000 revolution loss test, only 8.4% of the adsorbent particles prepared in Example 7 meet the requirements and have fluidization characteristics. This is because the structure of the mixed material is relatively dense after extrusion, so the calcium-based adsorbent obtained after extrusion has wear resistance compared to that without extrusion, and is easy to fluidize and circulate in the calcium circulation system.
[0078] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0079] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a calcium-based adsorbent, characterized in that: The following steps are involved: preparing a pore-forming agent solution; wherein the pore-forming agent in the pore-forming agent solution is biological glue; Mixing the calcium source, the binder and the pore-forming agent solution uniformly to obtain a mixed solution; removing the solvent from the mixed solution to obtain a mixed material; The mixed material is calcined until the pore former in the mixed material is decomposed to obtain the calcium-based adsorbent.
2. The method for preparing a calcium-based adsorbent according to claim 1, characterized in that: The biological glue is one or more of gelatin, bone glue, pectin and hide glue.
3. The method for preparing a calcium-based adsorbent according to claim 1, characterized in that: The calcium source is solid waste containing calcium; and the binder is cement.
4. The method for preparing a calcium-based adsorbent according to claim 1, characterized in that: In the mixed solution, the mass ratio of the pore former, the binder and the calcium source is (2.5-25):5:(20-42.5).
5. The method for preparing a calcium-based adsorbent according to claim 1, characterized in that: The calcination temperature is 600-800° C., and the calcination time is 1-2 h.
6. The method for preparing a calcium-based adsorbent according to claim 1, characterized in that: The following steps are also included: The material obtained after calcination is subjected to extrusion, grinding and screening to obtain the calcium-based adsorbent.
7. The method for preparing a calcium-based adsorbent according to claim 6, characterized in that: The extrusion pressure is 1-20 kN.
8. A calcium-based adsorbent, characterized in that: The calcium-based adsorbent is prepared by the preparation method of the calcium-based adsorbent according to any one of claims 1 to 7.
9. The calcium-based adsorbent according to claim 8, characterized in that The particle size of the calcium-based adsorbent is 0.25-0.38 mm.
10. Use of the calcium-based adsorbent according to any one of claims 8 to 9, characterized in that: The calcium-based adsorbent is used for cyclic adsorption of carbon dioxide.
Citation Information
Cited By
Calcium-based adsorbent as well as preparation method and application thereof
CN120437954A